2011
DOI: 10.1161/atvbaha.110.214585
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima-Media Thickness in Psoriatic Arthritis

Abstract: on behalf of the CaRRDs study group Objective-Subjects with psoriatic arthritis (PsA) have an abnormally high prevalence of vascular risk factors (VRFs) and are predisposed to vascular mortality. Tumor necrosis factor (TNF)-␣, a major determinant of inflammation, is involved in atherosclerosis. Ultrasonographic carotid intima-media thickness (C-IMT) evaluation allows for subclinical atherosclerosis detection. Methods and Results-Two hundred twenty-four PsA patients (120 on TNF-␣ blockers and 104 on traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 111 publications
(37 citation statements)
references
References 30 publications
1
34
0
1
Order By: Relevance
“…However, such an association does not entirely explain the extent of premature atherosclerosis in subjects with rheumatic diseases, and inflammation appears to act synergistically with traditional vascular risk factors (VRFs). In fact, several studies demonstrated that patients with rheumatic diseases had increased platelet reactivity [68], a higher grade of subclinical atherosclerosis [4, 9], impairment of endothelial function, and arterial stiffness [1012], as compared with control subjects matched for CV risk factors. In this setting, antirheumatic treatment was demonstrated to have beneficial effects on lowering the CV risk in these patients by controlling systemic inflammation, with maximum effect in those who achieved MDA [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such an association does not entirely explain the extent of premature atherosclerosis in subjects with rheumatic diseases, and inflammation appears to act synergistically with traditional vascular risk factors (VRFs). In fact, several studies demonstrated that patients with rheumatic diseases had increased platelet reactivity [68], a higher grade of subclinical atherosclerosis [4, 9], impairment of endothelial function, and arterial stiffness [1012], as compared with control subjects matched for CV risk factors. In this setting, antirheumatic treatment was demonstrated to have beneficial effects on lowering the CV risk in these patients by controlling systemic inflammation, with maximum effect in those who achieved MDA [8].…”
Section: Discussionmentioning
confidence: 99%
“…Besides articular manifestations, PsA and RA are characterized by an increased cardiovascular (CV) risk [3, 4], as represented by a higher prevalence of metabolic syndrome and of some of its major features (obesity, hypertension, hypercholesterolemia, hypertriglyceridemia, impaired fasting glucose) [5], increased platelet reactivity [68], higher degree of subclinical atherosclerosis [4, 9], impairment of endothelial function, and arterial stiffness [1012]. In particular, several studies have shown a higher prevalence of obesity in patient with PsA and patients with RA than in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Intervention studies (10) support such formulation. On the other hand, major markers of atherosclerosis (carotid intima-media thickness and hepatic steatosis) that assess the global damage secondary to metabolic and inflammatory determinants (24) are severely affected in PsA subjects (2,13,25). These data provide the rationale for testing whether, among PsA subjects starting a treatment with TNF␣ blockers, obesity would impact achieving MDA and s-MDA.…”
Section: Discussionmentioning
confidence: 99%
“…For all enrolled subjects, exclusion criteria were the lack of informed consent signature, age Ͻ18 years, previous treatment with TNF␣ blockers, malignancy, hematologic diseases, autoimmune diseases other than PsA, unstable medical conditions, and ongoing pregnancy. After informed consent signature, data about age, sex, height, weight, disease duration, disease activity, previous and/or current treatments, and VRFs were collected from all patients as previously described (13). According to current guidelines (14), obesity was defined as a body mass index (BMI) Ͼ30 kg/m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…They were found to have thinner carotid intima-media thickness compared to those who were treated with DMARDs (Di Minno et al, 2011). With these findings, it is possible that control of chronic inflammation in these patients may have a significant role in preventing vasculopathy.…”
Section: Introductionmentioning
confidence: 95%